PARAMETRIC STUDY ON INSET FEED SINGLE PATCH ANTENNA WITH DEFECTED GROUND STRUCTURE FOR MICROWAVE IMAGING SYSTEM - CHEE, KA CHIN (Universiti Malaysia Sarawak, (UNIMAS), 2019)
In microwave imaging system, the transmitted signal with high resolution requirement becomes a dominant factor in limiting the quality of transmitted or received signal. The microstrip antenna is one of the important equipment in the microwave imaging system due to its ability to transmit and receive signal. However, problems occurred in the microstrip antenna where the radiation efficiency decreased which affect the performance degradation once the microwave imaging system activated. The reasons for performance degradation including the decrease of gain, impedance mismatching and the radiation pattern is differ from the accurate pattern. Therefore, the Defected Ground Structure (DGS) is applied in the microstrip antenna design for microwave imaging system to enhance the features of microstrip antenna. Square Microstrip Patch Antenna with notch is proposed in order to achieve the high resolution requirements of the microwave imaging system such as high gain and high power handling capabilities. The proposed antenna use microstrip feed line as the feeding technique which connected directly to the patch antenna. This type of proposed antenna is designed on the substrate dielectric material FR-4 that having dielectric constant, ℇr = 4.7 and thickness, 1.6mm. The dumbbell shaped DGS is proposed as the resonant structures in this project. The varying of the different location and size of dumbbell shaped DGS under the microstrip line and the varying of the different size of dumbbell shaped DGS under the patch are simulated and then the best designs from these two simulations are combined as the finalized design. The result of return loss, radiation pattern and antenna gain are simulated by using Computer Simulation Technology (CST) Microwave Studio. The combinational design or the finalized design shows the better performance than the conventional design with the return loss of -38.99 dB and the higher antenna gain of 6.20 dB than the conventional design which with the return loss of -30.21 dB and the antenna gain of 5.48 dB. The finalized design is then fabricated and measured by using Wave and Antenna Training System (WATS 2002) to compare the radiation pattern. However, the measurement result are differ from the simulation result due to calibration, environmental issue, antenna type used at receiver and line of sight (LOS).